2015
DOI: 10.1186/s12891-015-0815-8
|View full text |Cite|
|
Sign up to set email alerts
|

A Bayesian network meta-analysis: Comparing the clinical effectiveness of local corticosteroid injections using different treatment strategies for carpal tunnel syndrome

Abstract: BackgroundLocal corticosteroid injections are commonly used to improve the short-term symptomatic severity and the functional status of the hands affected by carpal tunnel syndrome. We conducted a systematic review and Bayesian network-meta-analysis to compare the clinical effectiveness of local corticosteroid injections using different injection approaches.MethodsElectronic literature in Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, Web of Science, and other sources were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 55 publications
0
34
0
1
Order By: Relevance
“…In 2007, a systematic review [14] including 671 participants from 12 studies concluded that corticosteroid injection provided short-term symptom relief in contrast to placebo injection. In 2015, a network meta-analysis [35] with 633 patients from 10 studies compared the effectiveness of corticosteroid injections, using different injection approaches. Their analysis indicated that the ultrasound-guided in-plane injection method through the ulnar aspect of the wrist was the best approach in CTS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, a systematic review [14] including 671 participants from 12 studies concluded that corticosteroid injection provided short-term symptom relief in contrast to placebo injection. In 2015, a network meta-analysis [35] with 633 patients from 10 studies compared the effectiveness of corticosteroid injections, using different injection approaches. Their analysis indicated that the ultrasound-guided in-plane injection method through the ulnar aspect of the wrist was the best approach in CTS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for the application of this treatment is the ability of corticosteroids to reduce swelling, thereby improving the spatial relation between the carpal tunnel and the median nerve and tendons. Some scholars demonstrated that the injection of corticosteroids into the common flexor sheath and flexor pollicis longus tendon sheath can effectively relieve pain of CTS patients, improve functional impairment, and delay the need for surgery [6,17,18,19,20]. Advancements in ultrasonography allow the visualization of the structures of the carpal tunnel, including the median nerve, flexor tendons, and the TCL as well as the structures at risk, including the ulnar artery and the proximal palmar arch.…”
Section: Discussionmentioning
confidence: 99%
“…Нервно-мышечные Б О Л Е З Н И Neuromuscular DISEASES клинических шкал в краткосрочном периоде наблю-дения [34]. Таким образом, локальное введение КС при СЗК под УЗ-контролем методом in plane позволя-ет выполнить процедуру более точно, достоверно увеличивает эффективность лечения и снижает риск осложнений.…”
Section: том 8 Volunclassified